Biochemical and Fatty Acids Composition of Water Buffalo (Bubalus Bubalis) Follicular Fluid - Vencato, J.; Badon, T.; Bedin, S.; Cogo, P.; Simonato, M.; Stelletta, C. (Journal of Buffalo Science, 2014)
Aim of this study was to characterize the biochemical and fatty acids composition of follicular fluid collected from follicles of different sizes and in different phases of ovarian cycle in water buffalo farmed in Italy. Ovaries were collected at slaughterhouse during the breeding season; follicular fluid was aspirated dividing samples in small and large follicles (< 6 mm and > 6 mm respectively) and in luteal and follicular phase. Biochemical analysis and gas-chromatography were performed. Biochemical and fatty acids composition were greatly influenced by both follicular dimension and phase of ovarian cycle. Biochemical composition and its variations were in agreement with previously study conducted in buffalo and other species. This is the first report of the fatty acids composition of buffalo follicular fluid. Twenty-two fatty acids were identified in follicular fluid; nine were saturated fatty acids, six monounsatured fatty acids and seven polyunsatured fatty acids. The most dominant fatty acids were linoleic acid, oleic acid, palmitic acid, stearic acid and arachidonic acid. All the identified fatty acids concentrations vary at least because of follicle dimension or phase, with the exception of γ-linoleic acid and arachidonic acid which concentrations remain stable in all classes.